2022
DOI: 10.3390/agronomy12020511
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Solution to Synthetic Fertilizers for the Starter Fertilization of Bread Wheat under Mediterranean Climatic Conditions

Abstract: Under the high temporal variability of the Mediterranean climate, the prompt emergence of wheat seedlings and early vigor are pivotal attributes, positively affecting the final grain yield. Phosphorus (P) fertilization at sowing is largely used in wheat cultivation to support the early-season growth and promote a more rapid crop establishment. While conventional farming can rely on a wide variety of synthetic fertilizers, the number of options available for the starter fertilization of organic wheat is restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Other studies found that fulvic acids increased the germination rate and growth speed of spring cereals [80], while humic substances improved the seedling vigor of wheat [81]. As for macronutrients, the key role that phosphate fertilizer plays in promoting early growth of different crops is well referenced [82][83][84]. Similarly, nitrogen and potassium can boost seedling vigor, as reported by a study conducted on tomatoes [85].…”
Section: Discussionmentioning
confidence: 89%
“…Other studies found that fulvic acids increased the germination rate and growth speed of spring cereals [80], while humic substances improved the seedling vigor of wheat [81]. As for macronutrients, the key role that phosphate fertilizer plays in promoting early growth of different crops is well referenced [82][83][84]. Similarly, nitrogen and potassium can boost seedling vigor, as reported by a study conducted on tomatoes [85].…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, vermicomposting products promote the growth of nematode-predatory fungi and encourage rhizobacteria to generate toxic enzymes and toxins. Furthermore, vermicompost tea applications have exhibited noteworthy efficacy in controlling phytoparasitic nematodes [3].…”
Section: Methods Of Organic Farmingmentioning
confidence: 99%
“…Therefore, the ambitious target of the primary sector for the future (and present) is to produce more food while impacting less on natural resources. In agriculture, efforts are being made in different directions including the reduction of chemical fertilizers’ use [ 28 , 29 , 30 ]. In this context, biostimulants are receiving a lot of attention from both researchers and farmers as natural substances able to enhance crop performances [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%